Study protocol of the multi-site randomised controlled REDALI-DEM trial - The effects of structured Relearning methods on Daily Living task performance of persons with Dementia - Voigt-Radloff Sebastian; Leonhart Rainer; Rikkert Marcel; Kessels Roy; Hüll Michael (BMC Geriatrics, 2011)
Abstract Background Evidence from pilot trials suggests that structured learning techniques may have positive effects on the performance of cognitive tasks, movement sequences or skills in patients with Alzheimer's disease. The purpose of this trial is to evaluate whether the usual method of learning by trial and error or the method of errorless learning demonstrate better effects on the performance of two selected daily living tasks six weeks after the intervention in people with mild to moderate dementia. Methods/Design A seven-centre single-blind, active-controlled design with a 1:1 randomisation for two parallel groups will include 175 persons diagnosed with Alzheimer's disease or mixed type dementia (MMSE 14-24), living at home, showing at least moderate need for assistance in instrumental activities of daily living; primary carer available and informed consent of patient and primary carer. Patients of both study arms will receive 15 one-hour-sessions at home by trained interventionists practising two daily living tasks individually selected. In one group the trial and error technique and in the other group the errorless learning method will be applied. Primary outcome is the task performance measured with the Task Performance Scale six weeks post treatment. Discussion The trial results will inform us to improve guidelines for instructing individuals with memory impairments. A user-friendly practice guideline will allow an efficient implementation of structured relearning techniques for a wide range of service providers in dementia care. Trial registration DRKS00003117